The Role The Diniyah Takmilyah Madrasah In Developing Character Learners - Tabroni, Imam; Mukti, Saepul (Jurnal Pendidikan dan Konseling (JPDK), 2022)
This study aims to identify and discover the role of MDT in growing the character of students. The moral degradation that appears today is the impact of negative behavior that develops in people’s lives that affect the character of children. The research design uses grounded theory with a qualitative approach. Data collection techniques by observation, interviews, and documentation. Data analysis was carried out during data collection, data reduction, data presentation and conclusion drawing and verification. The results showed that education at MDT played an important role in strengthening the character of students. The spiritual moral character contained in Islamic religious education taught at MDT. Spiritual moral character is strengthened through the implementation of the MDT curriculum, habituation activities, worship practice programs, and the momentum of Porsadin activities